2008
DOI: 10.1007/bf03191366
|View full text |Cite
|
Sign up to set email alerts
|

Tautological cycles on Jacobian varieties

Abstract: In this paper we study the algebraic structure of the Tautological ring of a Jacobian: by the use of hard-Lefschetz-primitive classes we construct convenient generators that allow us to list and describe all the possible structures that may occur (the explicit list is given for g ≤ 9 and for a few special curves).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…A celebrated result of Ceresa [Cer83] implies that for a generic curve C, the class of W d is not proportional to the class of Θ modulo algebraic equivalence. Beauville in [Bea04] (see also [Pol05,Mar08,Moo09]) has studied results about algebraic equivalence. We believe that the tautological subring of the ring of tropical cycles modulo algebraic equivalence is an interesting object to study.…”
Section: Introductionmentioning
confidence: 99%
“…A celebrated result of Ceresa [Cer83] implies that for a generic curve C, the class of W d is not proportional to the class of Θ modulo algebraic equivalence. Beauville in [Bea04] (see also [Pol05,Mar08,Moo09]) has studied results about algebraic equivalence. We believe that the tautological subring of the ring of tropical cycles modulo algebraic equivalence is an interesting object to study.…”
Section: Introductionmentioning
confidence: 99%
“…In [Seb13] it is proved that for one dimensional cycles on a variety dominated by a product of curves, smash equivalence and numerical equivalence coincide. The same result can be deduced from [Mar08] and [Her07], where it is shown that for a smooth projective curve C, for any adequate equivalence relation, [C]…”
Section: Introductionmentioning
confidence: 61%
“…24 in [8] or to Theorem 4 in [7], if p i alg 0 then p j alg 0 for j ≥ i. We generalize this to the case of rational equivalence in this section, which will be needed in the proof of Theorem 1.…”
Section: Preliminary Resultsmentioning
confidence: 99%